2016
DOI: 10.1042/bst20160120
|View full text |Cite
|
Sign up to set email alerts
|

Diaphanous-related formin 1 as a target for tumor therapy

Abstract: Formins nucleate actin and stabilize microtubules (MTs). Expression of the formin Diaphanous homolog 1 (DIAPH1) is increased in malignant colon carcinoma cells, while expression of DIAPH3 is up-regulated in breast and prostate carcinoma cells. Both DIAPH1 isoforms are required to stabilize interphase MTs of cancer cells, and it has been shown that loss of this function decreases the metastatic potential of these cells. Moreover, depletion of DIAPH3 increases the sensitivity of breast and prostate carcinoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…5a), together with the fact that it was listed as a putative target of miR-10b. Its potential disease-relevance was substantiated by its recent association with colon carcinoma, and its potential role in actin-organization and microtubule stabilization [35][36][37]. When re-analyzing normalized RNA-seq data generated by Cho et al, retrieved from GEOrepository (GSE111582), both, DIAPH2 and HOXD10, showed lower expression in RDEB-cSCC versus RDEB-skin tissue [8], ( Supplementary Fig.…”
Section: Diaph2 Is Deregulated In Rdeb-cscc and Predicted To Be A Tarmentioning
confidence: 95%
“…5a), together with the fact that it was listed as a putative target of miR-10b. Its potential disease-relevance was substantiated by its recent association with colon carcinoma, and its potential role in actin-organization and microtubule stabilization [35][36][37]. When re-analyzing normalized RNA-seq data generated by Cho et al, retrieved from GEOrepository (GSE111582), both, DIAPH2 and HOXD10, showed lower expression in RDEB-cSCC versus RDEB-skin tissue [8], ( Supplementary Fig.…”
Section: Diaph2 Is Deregulated In Rdeb-cscc and Predicted To Be A Tarmentioning
confidence: 95%
“…We nominated diaphanous related formin 2 ( DIAPH2) for further evaluation based on significant differences in Kaplan Meier survival curves (p < 0.05, log-rank test, Figure 5A), together with the fact that it was listed as a putative target of miR-10b. Its potential disease-relevance was substantiated by its recent association with colon carcinoma, and its potential role in actin-organization and microtubule stabilization (35-37). When re-analyzing normalized RNA-seq data generated by Cho et al , retrieved from GEO-repository (GSE111582), both, DIAPH2 and HOXD10 , showed lower expression in RDEB-SCC versus RDEB-skin tissue (8, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that DIAPH3, as a substrate of RNF216, also plays a central role in promoting the growth and metastasis of cholangiocarcinoma. Although DIAPH3 has been reported to be involved in the growth and metastasis of a variety of tumors (34,35,(39)(40)(41), its role in cholangiocarcinoma is not explicit. We elaborated the regulatory upstream of DIAPH3.…”
Section: Dicussionmentioning
confidence: 99%